Influence of the ventilatory mode on acute adverse effects and facial thermography after noninvasive ventilation - Pontes,Suzy Maria Montenegro (2017)
ABSTRACT Objective: To compare the incidence and intensity of acute adverse effects and the variation in the temperature of facial skin by thermography after the use of noninvasive ventilation (NIV). Methods: We included 20 healthy volunteers receiving NIV via oronasal mask for 1 h. The volunteers were randomly divided into two groups according to the ventilatory mode: bilevel positive airway pressure (BiPAP) or continuous positive airway pressure (CPAP). Facial thermography was performed in order to determine the temperature of the face where it was in contact with the mask and of the nasal dorsum at various time points. After removal of the mask, the volunteers completed a questionnaire about adverse effects of NIV. Results: The incidence and intensity of acute adverse effects were higher in the individuals receiving BiPAP than in those receiving CPAP (16.1% vs. 5.6%). Thermographic analysis showed a significant cooling of the facial skin in the two regions of interest immediately after removal of the mask. The more intense acute adverse effects occurred predominantly among the participants in whom the decrease in the mean temperature of the nasal dorsum was lower (14.4% vs. 7.2%). The thermographic visual analysis of the zones of cooling and heating on the face identified areas of hypoperfusion or reactive hyperemia. Conclusions: The use of BiPAP mode was associated with a higher incidence and intensity of NIV-related acute adverse effects. There was an association between acute adverse effects and less cooling of the nasal dorsum immediately after removal of the mask. Cutaneous thermography can be an additional tool to detect adverse effects that the use of NIV has on facial skin.